Caracterización del material particulado para determinar la calidad del aire en la Universidad Nacional de Trujillo, 2022 - Br. Acuña Jara, Diana Fiorella (2022)
ABSTRACT The objective of this research work is to characterize the particulate material to determine the quality of the air at the National University of Trujillo, in order to prevent the dangers of air pollution within our alma mater and prevent diseases, for which four monitoring points within the university, located in: Faculty of Pharmacy and Biochemistry, Faculty of Chemical Engineering, Central Library and the Faculty of Nursing, equipment such as Hi- Vol and weather station were used. The methodology used is in accordance with what is stated in the Environmental Quality Standards (ECA) for Air (D.S. N ° 003-2017 - MINAM), as well as the sampling in the field was done following the criteria established in the Quality Monitoring Protocol of Air and Data Management (R.D. N ° 1404-2005 - DIGESA / SA), where it was finally found that the Air Quality Index is oscillating within the values of 80.4 to 100, and according to Ministerial Resolution No. 181-2016-MINAM indicates that this range is within a moderate classification, in addition, it mentions that it is an acceptable range and complies with the Air ECA. KEY WORDS: Particulate matter, Hi-Vol, INCA, concentration, mass.